Mandi Pangir Menyambut Bulan Ramadhan Dalam Perspektif Hadis - Fadhil, Muhammad; Hidayat, Muhammad (UIN Sumatera Utara Medan, 2024)
This research discusses the Mandi Pangir tradition in welcoming the holy month of Ramadan seen from a hadith perspective. The aim of this research is to find out how the Pangir Bathing tradition is usually carried out in the month of Ramadan. And to find out the hadith's view of the pangir bath in the month of Ramadan. The focus of this research is looking at the tradition of mandi pangir developing in society, how the tradition of marpangir in welcoming Ramadhan is carried out by the community, and how the opinions of experts in the field respond to the mandi pangir tradition. Religion and Community Figures, then supported by literature studies related to theoretical opinions. From the results of field research, it was found that the marpangir tradition is a hereditary tradition that has existed since ancient times. Based on quotes from hadiths relating to cleanliness, fragrance, health and joy in welcoming the holy month of Ramadan regarding the tradition of bathing in Pangir, it can be concluded that the tradition of bathing in Pangir is not prohibited if it is carried out according to Islamic teachings. The pangir bathing tradition is just a custom that is carried out because of feelings of joy in welcoming the holy month of Ramadan.